Establishing model uncertainty of SLS reinforced concrete crack models applied to load-induced cracking - Christina Helen McLeod (Acta Polytechnica CTU Proceedings)
Although some research has been performed, serviceability limit state (SLS) concrete crack models have yet to be calibrated fully in probabilistic terms in structural design standards. This is partly due to the fact that the SLS is generally not the critical limit state in structural design. However, in some specialist structures such as water retaining structures, the SLS such as cracking is the limiting design criterion, specifically the crack width required to control leakage and thus requires a proper probabilistic analysis. In probabilistic crack models, the reliability of the crack model is determined by the performance function whereby the design limiting crack width is greater than the estimated crack width calculated using the appropriate design crack model. As cracking in concrete is a random mechanism with a high degree of variability and crack models tend to be at least semi-empirical with inherent uncertainty, model uncertainty of the crack model is significant and is applied in the reliability model as a random variable. A database was established of both short and long term cracking experimental data for the tension load case to quantify model uncertainty. However, the data for long term cracking is limited which meant that the model uncertainty in this case was not definitively established. This paper discusses the determination of model uncertainty for tension cracking, which could be extrapolated to other models where data is limited.